2021
DOI: 10.1016/j.jsams.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Thigh muscle activation patterns and dynamic knee valgus at peak ground reaction force during drop jump landings: Reliability, youth competitive alpine skiing-specific reference values and relation to knee overuse complaints

Abstract: et al., Thigh muscle activation patterns and dynamic knee valgus at peak ground reaction force during drop jump landings: reliability, youth competitive alpine skiing-specific reference values and relation to knee overuse complaints,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Thus, as suggested by Jordan et al [ 34 ], a plausible complementary assessment approach could be found in rapid, voluntary, and maximal-isometric hamstrings/quadriceps contractions, an approach that would allow maximum torque (MVC) and rate of torque development (RTD) to be determined. Moreover, as it is known that the (pre)activation levels of the hamstring muscles are modifiable and play a crucial role in jump landing-related ACL injury mechanisms [ 35 ], the quantification of the activation patterns of the thigh muscles during drop-jump landings as proposed by Ellenberger et al [ 36 ] could also represent a conceivable additional screening approach.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as suggested by Jordan et al [ 34 ], a plausible complementary assessment approach could be found in rapid, voluntary, and maximal-isometric hamstrings/quadriceps contractions, an approach that would allow maximum torque (MVC) and rate of torque development (RTD) to be determined. Moreover, as it is known that the (pre)activation levels of the hamstring muscles are modifiable and play a crucial role in jump landing-related ACL injury mechanisms [ 35 ], the quantification of the activation patterns of the thigh muscles during drop-jump landings as proposed by Ellenberger et al [ 36 ] could also represent a conceivable additional screening approach.…”
Section: Discussionmentioning
confidence: 99%